PEMANFAATAN E-LEARNING DALAM PEMBELAJARAN MATEMATIKA SECARA MANDIRI - Nurhawani Sitompul; elvi rosalinda siagian; fatima sari; khoirunniasa .; yuni rhamayanti (Jurnal Cermatika, 2021)
Basically, the use of E-learning in mathematics education is broad, both as a medium of learning in the classroom and as a medium for independent learning. Utilization of E-Learning will improve learning outcomes indirectly. Thus, it is hoped that the internet speed available on the campus, especially the Graha Nusantara University (UGN) Padangsidimpuan, is very good so that the implementation of self-learning based on E-Learning can run smoothly. In addition, all training is needed in the context of socializing the development of E-Learning learning methods so that students have effective thinking patterns and accept E-Learning as an alternative learning and evaluation in teaching and learning.